A multi‐century meteo‐hydrological analysis for the Adda river basin (Central Alps). Part II: Daily runoff (1845–2016) at different scales. (3rd July 2020) - Ranzi, Roberto; Michailidi, Eleni M.; Tomirotti, Massimo; Crespi, Alice; Brunetti, Michele; Maugeri, Maurizio
Abstract: A high‐quality daily runoff time series of the Lake Como inflow and outflow, the longest for Italian Alps, was reconstructed for the 1845–2016 period in the Adda river basin. It was compared with contemporary monthly precipitation and temperature observations and estimated potential evapotranspiration losses. Trend analyses were conducted for daily flow maxima and 7‐day duration minima of inflows into the lake showing a non‐significant decrease and a significant increase, respectively. Although the annual precipitation time series exhibits a non‐significant decrease, annual runoff volumes decrease with a rate of −136 mm⋅century −1, with a significance level of 5%. Possible causes of variability of rainfall and runoff as North Atlantic Oscillation (NAO), Atlantic Multidecadal Oscillation and Western Mediterranean Oscillation indexes and sunspot activity were also explored. Wavelet spectra analyses of monthly precipitation and runoff show some changes in the energy both at small and large scales and are effective in pointing out phenomena as droughts and the effects of dams' regulation. Conversely, wavelet coherence spectra indicate a weak correlation of NAO and sunspots with precipitation. In addition, the analysis of temperature and potential evapotranspiration tendencies suggests that the decrease of runoff has to be ascribed mostly to anthropogenic factors, including water abstraction for irrigation and increased evapotranspiration losses due to natural afforestation and, only in part, to climatic variability. Abstract : The article presents the reconstructed daily runoff series of the Lake Como inflow and outflow for the 1845–2016 period in the Adda river basin, which is the longest runoff record of Italian Alps. It was investigated for trend and variability over different time scales and compared with the basin precipitation record presented in the companion paper. Annual runoff volumes show a significant decrease, ascribing mostly to increasing evapotranspiration losses and anthropic factors.